2021
DOI: 10.3389/fneur.2021.693318
|View full text |Cite
|
Sign up to set email alerts
|

High Neutrophil–Lymphocyte Ratio Predicts Post-stroke Cognitive Impairment in Acute Ischemic Stroke Patients

Abstract: Background and Aims: Systemic inflammation is associated with an increased risk of cognitive impairment and dementia, but the associations between them in stroke patients are less clear. We examined the impact of systemic inflammation represented as the neutrophil-lymphocyte ratio (NLR) on the development of post-stroke cognitive impairment (PSCI) and domain-specific cognitive outcomes 3-month after ischemic stroke.Methods: Using prospective stroke registry data, we consecutively enrolled 345 participants with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 32 publications
1
37
0
Order By: Relevance
“…Patient sex, age, and the NIHSS score were considered to be associated with the occurrence of PSCI in previous studies ( 29 – 31 ). Few studies have considered using the NLR as an easily available peripheral inflammatory factor, and its relationship to PSCI ( 19 ). Our results suggest that higher NLR levels at admission are associated with the presence of PSCI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patient sex, age, and the NIHSS score were considered to be associated with the occurrence of PSCI in previous studies ( 29 – 31 ). Few studies have considered using the NLR as an easily available peripheral inflammatory factor, and its relationship to PSCI ( 19 ). Our results suggest that higher NLR levels at admission are associated with the presence of PSCI.…”
Section: Discussionmentioning
confidence: 99%
“…The NLR, as an inflammatory marker, is associated with cognitive impairment ( 25 , 26 ). There are few studies on the association between the NLR and PSCI, except for the study by Minwoo Lee et al ( 19 ) who found that the NLR in acute ischemic stroke was independently associated with PSCI at 3 months poststroke. Nomograms have been widely used to predict the prognosis of oncology patients, predicting patient survival based on a simple score.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, lymphocyte count and classification are signs of the body's immune activity. With the discovery of the value of the neutrophil-lymphocyte ratio in the long-term predictive value of post-stroke cognitive impairment (Lee et al, 2021), the damage to the vascular nerve unit and cognitive dysfunction mediated by immune responses need to be further studied.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, much research effort is devoted to identify possible low cost, and highly efficient, biological markers of preclinical dementia, in order to allow a precision medicine approach. In the recent past, the importance of leukocyte counts and their derived ratios has been established [22] in several fields of clinical medicine, as markers of disease progression, predictors of outcomes, and even of cognitive impairment after acute ischemic stroke [23].…”
Section: Discussionmentioning
confidence: 99%